Pengaruh Permainan Monopoli dalam Peningkatan Pengetahuan, Sikap, dan Tindakan Pola Konsumsi Buah dan Sayur Pada Siswa SDN 021 Sungai Kunjang Samarinda - Marini, Anisa; Wirapuspita, Ratih; Kamaruddin, Iriyani (HIGIENE: Jurnal Kesehatan Lingkungan, 2015)
Childrend in general didn’t like consumed vegetables and fruits, the levels of fruit and vegetables consumption in children was low. Game was one of its media to gaves information that was fun for children, one of them was monopoly. Therefore, need for recogninition of compsumption pattern of fruits and vegetables throught the game would improved the knowledge,attitudes and actions of the consumption pattern of fruits and vegetables.This research aimed to determine the effect monopoly game increase of knowledge, attitude and actions consumption pattern of fruits and vegetables to students SDN 021 Sungai Kunjang, Samarinda using quasy eksperiment with pretest-posttest with control group and an experimental group and a large sample of 32 students in each class control and 43 students in the eksperimental group. Sampling techniques is purposive sampling and data analisis using the paired T-test, wilcoxon test,dan man whitney test with significance < 0,05. The results showed that there were significant knowledge ( value=0.000), attitude ( value=0.000) and actions ( value=0.000) of students before and after the intervention of monopoly game to increase knowledge, attitude dan actions of fruits and vegetables to students SDN 021 Sungai Kunjang Samarinda.The suggestion of this research were cooperation between the school and the parents, and the guidance from health The suggestion of this research were cooperation between the school and the parents, and the guidance from health care worker about the importance to eating fruits and vegetables to students to conduct training joint cooperation of UKS and small doctor in school. Key Words : Monopoly, Knowledge, Attitude and Actions